Characteristic analysis of ecosystem service value of water system in Taiyuan urban district based on LUCC - Ping, Liu; Xiuqing, Zheng; Junfeng, Chen; Qing, Zhang; Jingling, Li; Bo, Wu (International Journal of Agricultural and Biological Engineering, 2016)
Changes in the land use and ecosystem service value of the 600 m buffer zone of Jinyang Lake and the 1000 m riparian zone of the Fenhe River in the Taiyuan urban district in China, were studied using satellite image data collected in June 2006 and June 2013. According to the ecosystem services assessment system based on expert knowledge, the ecosystem service value (ESV) per unit area was determined for various land-use types and the value of the water system and its buffer regions in the Taiyuan urban district were determined. And then the relationship between LUCC (Land Use/Cover Change) and ESV was discussed. Moreover, the accuracy and validity of the results was analyzed. The results showed that: (1) the areas of green vegetation and water bodies of Jinyang Lake and its buffer region decreased by 24.96% and 3.22%, respectively, between June 2006 and June 2013, whereas the areas of farmland and built-up land increased by 15.81% and 12.37%, respectively. At Jinyang Lake, the degree of dynamic change for green vegetation, water bodies, farmland, built-up land, and unused land was −0.13, −0.02, 0.17, 0.09, and −0.05, respectively. In the Fenhe River’s buffer region, the areas of green vegetation, farmland and unused land decreased by 1.36%, 6.36% and 0.3%, respectively, but those of built-up land and water bodies increased by 1.41% and 6.61%, respectively. Their degree of dynamic change was −0.03, −0.02, −0.04, 0.01 and 0.32, respectively; (2) In 2006, the landscape fragmentation indices (LFI) of Jinyang Lake buffer of 0-200 m zone were greater than 2, but those of 200-600 m buffer zone were less than 0.3, the water-body index not included. However, in 2013, the landscape fragmentation indices of green vegetation and water bodies of 0-600 m buffer zone were both high, meaning that the land-use pattern had improved. The fragmentation index of green vegetation of the 0-200 m buffer increased from 0.1 (the minimum for the year) to 1.7 (the maximum for the year) during the seven years of this study along the Fenhe River. The fragmentation index of built-up land increased from 0.007 to 0.01 in the 200-500 m buffer and from 0.007 to 0.06 in the 500–1000 m buffer. (3) The total ecosystem service value of Jinyang Lake and its buffer region decreased by 22.673%, whereas during the same period, that of the Fenhe River and its buffer region increased by 41.345%. The total ecosystem service value of the water bodies and their buffer regions in the Taiyuan urban area increased by 13.725% overall. (4) The change rate of the ecosystem service value of the 0-600 m buffer region decreased by 1.579% at Jinyang Lake, while that of the 0-1000 m buffer region increased 5.079% at the Fenhe River over the seven years.Keywords: remote sensing, water system, land use, LUCC, ecosystem service value, urbanDOI: 10.3965/j.ijabe.20160901.2021Citation: Liu P, Zheng X Q, Chen J F, Zhang Q, Li J L, Wu B. Characteristic analysis of ecosystem service value of water system in Taiyuan urban district based on LUCC. Int J Agric & Biol Eng, 2016; 9(1): 153－165.